Infliximab in the treatment of plaque type psoriasis - Rosita Saraceno; Andrea Saggini; Lucia Pietroleonardo; Sergio Chimenti (Dove Medical Press, 2009)
Rosita Saraceno, Andrea Saggini, Lucia Pietroleonardo, Sergio ChimentiDepartment of Dermatology, University of Rome Tor Vergata, Rome, Viale Oxford 81, Rome, ItalyAbstract: Psoriasis is a chronic and immunomediated skin disease characterized by erythematous scaly plaques. Psoriasis affects approximately 1% to 3% of the Caucasian population. Tumor necrosis factor alpha (TNF-α) is a proinflammatory cytokine that plays a critical role in the pathogenesis of psoriasis. Infliximab is an anti-TNF-α drug widely used for the treatment of plaque type psoriasis and psoriatic arthritis. Controlled clinical trials demonstrated that infliximab is characterized by a high degree of clinical response in moderate to severe plaque psoriasis. Moreover infliximab showed rapid efficacy in nail psoriasis which represents a therapeutic challenge for dermatologists and a relevant source of distress for patients with plaque psoriasis. This anti-TNF-α has an encouraging safety profile, especially as long as physicians are watchful in prevention and early diagnosis of infections and infuse reactions. The efficacy, tolerability and safety profiles suggest infliximab as a suitable anti-psoriatic drug in the long-term treatment of a chronic disease such as plaque-type psoriasis.Keywords: psoriasis, nail psoriasis, infliximab, long-term treatment